2019
DOI: 10.1088/1361-6595/ab2b1d
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Evidence of ion energy distribution shift in HiPIMS plasmas with positive pulse (2019 Plasma Sources Sci. Technol. 28 01LT03)

Abstract: Figure 3. Time-integrated EDFs of Nb + for the case without PP, +50 V PP of 100 μs, and 250 μs duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…From these data it is clear that the group P2 presents a constant energy shift of about 22 eV with the group P3 for all experiments when U + is applied to the target. Such energy shift has been reported in the literature [52,54,55].…”
Section: Ion Energy Groupssupporting
confidence: 81%
See 1 more Smart Citation
“…From these data it is clear that the group P2 presents a constant energy shift of about 22 eV with the group P3 for all experiments when U + is applied to the target. Such energy shift has been reported in the literature [52,54,55].…”
Section: Ion Energy Groupssupporting
confidence: 81%
“…• Group P2: Two hypotheses can be formulated to explain this high energy group. First, it can be attributed to the plasma-off time where the plasma potential settles at relatively small positive value [52]. It results in acceleration of ions to a slightly higher energy.…”
Section: Ion Energy Groupsmentioning
confidence: 99%
“…In this pulsing scheme ions generated during the negative voltage pulse are accelerated towards the substrate during the positive voltage pulse [12,13]. Mass-spectrometry studies [13][14][15][16][17][18][19][20][21][22][23] have shown that the ion energy gain is proportional to the applied positive voltage U + and the high-energy peak in the recorded IEDFs is roughly at an energy of ΔE acc = qU + . Some studies [15,[19][20][21]23] also observed additional distinct peak/peaks in the recorded IEDFs at lower energies.…”
Section: Introductionmentioning
confidence: 99%